Determine the operation of a firewall to block avoidance internet censorship systems based on proxy - Romero Goyzueta, Christian Augusto (2016)
Within the policies of an organization is possible find not to allow users to access sites on the Internet for entertainment or social networks, as in the case of production organizations and educational therefore a firewall that is used implemented certain rules based on the policies of the organization, blocks access to certain defined sites while you let others free. However there is no implemented rules to block proxies of Avoidance Internet Censorship Systems, the user can access easily to those proxies. The addresses of these proxies change very frequently, so it is almost impossible to block them all, and eventually they appear more. The proposed solution is to create a firewall that uses dynamic rules, these rules are created for the dynamic firewall. A test of each address to a destination is made and if it finds that the destination is a proxy of one of these evation systems; the firewall creates a new rule and automatically implemented. In this way the user will lose access to the proxy.